2003
DOI: 10.1016/s0010-7824(02)00537-1
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study over 13 cycles to assess the influence of oral contraceptives containing ethinylestradiol combined with drospirenone or desogestrel on carbohydrate metabolism

Abstract: In this open-label, randomized study we compared the influence of a new oral contraceptive containing 30 µg ethinylestradiol and 3 mg drospirenone (Yasmin™) with a reference preparation containing 30 µg ethinylestradiol and 150 µg desogestrel (Marvelon™) on variables of carbohydrate metabolism by means of oral glucose tolerance tests at baseline and in the 6th and 13th treatment cycle. The mean levels of fasting glucose and insulin were similar at baseline and after 13 treatment cycles, whereas C-peptide and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
2
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 32 publications
2
35
2
5
Order By: Relevance
“…In contrast, drospirenone has demonstrated positive effects on lipid profiles including increasing HDL [42, 45, 46] and decreasing LDL [42, 46]. We did not observe these same changes across an OCP cycle in the current study.…”
Section: Discussioncontrasting
confidence: 74%
“…In contrast, drospirenone has demonstrated positive effects on lipid profiles including increasing HDL [42, 45, 46] and decreasing LDL [42, 46]. We did not observe these same changes across an OCP cycle in the current study.…”
Section: Discussioncontrasting
confidence: 74%
“…While the carbohydrate metabolism was not affected significantly in this and various studies with EE and DRSP therapy (22,23,28), some studies showed a moderate impairment of glucose tolerance (26,29).…”
Section: Discussionmentioning
confidence: 54%
“…Drospirenone is a 17a-spirolactone derivative progestin that combines a potent progestogenic activity with antiandrogenic and antimineralocorticoid activity. The latter, by counteracting the stimulating action exerted by EE on the renin-aldosterone system, may reduce blood pressure (5). However, like other OCs, the pills containing drospirenone present such disadvantages as a requirement for daily administration, fluctuations in plasma contraceptive concentrations, hepatic first-pass metabolism, and potential gastrointestinal interference with absorption.…”
mentioning
confidence: 99%